A case report of successful retrieval of missing Cu T from peritoneal cavity in a case of pelvic Tuberculosis - Moitra, Bratati; Bhagat, Megha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The incidence of missing IUCD is 0.5-2%. Usually the cause is either expulsion or perforation of uterus. Sometimes the perforated IUCD remains asymptomatic for years and found incidentally later. We are hereby presenting a case of 35 years female P3 L3 who had Cu T insertion 3 years back. She was asymptomatic for more than 2 and ½ years and then presented with severe pain abdomen for which she was evaluated and exploratory laparotomy was done and Cu T was found embedded in the serosa of rectosigmoid colon which was covered by dense omental adhesions